Collagen peptide promotes DSS-induced colitis by disturbing gut microbiota and regulation of macrophage polarization - Li, Xiaoxia; Cui, Luwen; Feng, Guilin; Yu, Shengnan; Shao, Guanglong; He, Ningning; Li, Shangyong (Frontiers in Nutrition, 2022)
Ulcerative colitis (UC) is an inflammatory bowel disease caused by mucosal immune system disorder, which has increased steadily all over the world. Previous studies have shown that collagen peptide (CP) has various biological activities, while its effect on UC is unclear. In this study, 2.5% dextran sulfate sodium (DSS) was used to establish acute colitis in mice. Our results suggested that CP supplementation (200, 400 mg/kg/day) promoted the progression of colitis, increased the expression of inflammatory factors and the infiltration of colonic lamina propria macrophages. Gut microbiota analysis showed the composition changed significantly and inflammation promoted bacteria was after CP treatment. Meanwhile, the effect of CP on macrophage polarization was further determined in Raw264.7 cell line. The results showed that CP treatment could increase the polarization of M1 macrophages and promote the expression of inflammatory factors. In conclusion, our results showed that CP treatment could disrupt the gut microbiota of host, promote macrophage activation and aggravate DSS-induced colitis. This may suggest that patients with intestinal inflammation should not take marine derived CP.